2009
DOI: 10.1103/physrevd.79.074018
|View full text |Cite
|
Sign up to set email alerts
|

Double charmonium production atBfactories within light cone formalism

Abstract: ′ c within light cone formalism. It is shown that if one disregards the contribution of higher fock states, the twist-3 distribution amplitudes needed in the calculation can be unambiguously determined from the twist-2 distribution amplitudes and equations of motion. Using models of the twist-2 distribution amplitudes the cross sections of the processes under study have been calculated. The results of the calculation are in agreement with Belle and BaBar experiments. It is also shown that relativistic and radi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 52 publications
1
34
1
Order By: Relevance
“…The values of the constants f ηc , f η ′ c were calculated in paper [24]. The values of the constants of the P -wave charmonia mesons can be found in paper [16].…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The values of the constants f ηc , f η ′ c were calculated in paper [24]. The values of the constants of the P -wave charmonia mesons can be found in paper [16].…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The original lowest-order (LO) NRQCD predictions to this process [10,11] is about 1 order of magnitude smaller than the measurement [1]. This alarming discrepancy has triggered a great amount of theoretical investigations in both NRQCD and light-cone approaches [12][13][14][15][16][17][18][19][20][21][22]. One crucial element in alleviating the discrepancy between the NRQCD prediction and the data is the substantial and positive next-to-leading-order (NLO) perturbative corrections [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that this approximation cannot be considered as reliable. This conclusion can be drawn from the experience obtained in the study of double charmonium production at B factories [20], which tells us that relativistic and radiative corrections to double charmonia production can be very large. Nevertheless, in this paper the leading order approximation of NRQCD will be used to get an independent estimation of the widths of the exclusive bottomonia decays under study.…”
Section: Description Of the Calculation Proceduresmentioning
confidence: 65%
“…There were many attempts to resolve this discrepancy [7][8][9][10][11][12][13][14][15][16][17]. Lately, it has been shown that the agreement between theory and experiment can be achieved if one takes into account radiative and relativistic corrections to the cross sections [18][19][20].…”
Section: Introductionmentioning
confidence: 98%